THE INFLUENCE OF PERSONALITY MODELING DEVELOPMENT ON PRESCHOOL CHILDREN'S AGGRESSIVE BEHAVIOR - Deasy Dwi Cahyaningtyas Arifin (Jurnal Scientia, 2023)
Aggression is a physical or verbal behavior aimed at hurting others. Such harmful behavior, both physically and verbally, constitutes an antisocial action. Aggressive behavior is exhibited by children and adolescents, both at home, school, and even within the broader community. Mildly aggressive behavior in a child can be tolerated or ignored, but if it escalates, posing harm to oneself or others, it needs to be dealt with seriously as it can lead to more serious consequences. Preschool-age children experience significant individual development between the ages of 2 and 6. During this period, children attempt to control their environment and start learning to adjust rationally. The development of their behavioral aspects is observed to progress rapidly during the preschool years. In this context, the development of personality modeling is crucial in reducing aggressive behavior commonly seen in this age group. Learning through modeling involves imitating or modifying a behavior observed and generalizing it from one observation to another. The subjects of the study are typically boys and girls divided into two groups: an experimental group, which will receive personality modeling development treatment, and a control group, which will not receive any treatment. This discussion raises the hypothesis of whether there is a difference in the influence of personality modeling development between the experimental and control groups.